Spotlighting the roles of corporate social responsibility in the wake of covid-19: A Scoping review - LAABOUSSE , Soukaina; LAGDIM SOUSSI, Lalla Hind (Revue Internationale du Chercheur, 2023)
Purpose : The aim of this paper is to provide an organized review of research studies on the current development of CSR practices amid the covid-19 crisis. Methods : We conducted a scoping review, searching three databases with CSR and COVID-19 keywords. We screened titles, abstracts, and full-text using PRISMA-ScR. Results : Of 3,524 papers, 48 met eligibility criteria. Results show that CSR roles during COVID-19 affect social, environmental, economic, and societal aspects. Studies used quantitative or qualitative approaches. Importance of CSR during COVID-19 is associated with business performance, employee motivation, job security, and resilience. Conclusions : CSR contributes to sustainable solutions in crises, with analysis of relationships between CSR and business performance, employee motivation, and resilience.